CONSTRUCTION SPIN COATING AS PRINTING EDIBEL FILM GANYONG - Endah Kurnia Yuningsih; Tuti Kurniati; Neneng Windayani; Rizki Zakwandi; Tiana Azmi Alawiyah (Journal of Teaching and Learning Physics, 2017)
The existence of halal and good food is a basic requirement for Muslims. Maintaining the quality of food from the integrity of nutrients and keep it away from the source of disease is one effort to create good quality food. This will be more valuable if it can be done with natural materials that exist around the community itself. Growing environmental awareness and social sensitivity on the young generation of Muslims is something that can not be separated from education in college. This research is aimed to develop bio-plastic making device based on ganyong (Canna edulis) with the utilization of used and cheap goods. The method used in the research is Research and Development (R & D). Develop Spin Coating devices to suit the needs of edible printing. The effectiveness of measurable measurements of physical bio-plastic factor measurements resulted in strength, thickness and durability. The results of this study show that the results are quite optimal, especially on the thickness factor. The thickness of bio-plastics produced using modified spin coating is <0.5 mm with rotation at a certain speed, ie at 12 volts and 60o - 80oC. The result of bio-plastic obtained can be used as food wrapper which in this research is applied as dodol wrapping. So the quality of nutrition dodol can be more durable.